1997
DOI: 10.1111/j.1439-0396.1997.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fats on susceptibility of low‐density lipoproteins to lipid peroxidation in pigs

Abstract: Summary The present study investigated the effect of dietary fats rich in polyunsaturated fatty acids (soybean oil), mono‐unsaturated fatty acids (olive oil) and saturated fatty acids (beef tallow) on the susceptibility of low‐density lipoproteins (LDL) to lipid peroxidation in pigs. In a cross‐over design with three periods, nine pigs were fed each of the fats in daily amounts of 250 g for two weeks. The susceptibility of LDL to lipid peroxidation was determined by Cu2+‐catalysed oxidation. The lag phase befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It is well known that dietary PUFA increase the susceptibility of LDL to lipid peroxidation whereas dietary antioxidants, especially tocopherols, protect LDL against lipid peroxidation [12,42]. In disagreement with this study several others demonstrated that the administration of oils rich in PUFA, such as soybean oil, sunflower oil or corn oil, increase the susceptibility of LDL lipids in humans and animals as opposed to administering oils rich in MUFA such as olive oil or rapeseed oil [43][44][45][46]. The disagreement between the present results and those above-mentioned is well explainable by different vitamin E concentrations of the diets.…”
Section: Effect Of Different Fats On the Susceptibility Of Ldl To Lipmentioning
confidence: 76%
“…It is well known that dietary PUFA increase the susceptibility of LDL to lipid peroxidation whereas dietary antioxidants, especially tocopherols, protect LDL against lipid peroxidation [12,42]. In disagreement with this study several others demonstrated that the administration of oils rich in PUFA, such as soybean oil, sunflower oil or corn oil, increase the susceptibility of LDL lipids in humans and animals as opposed to administering oils rich in MUFA such as olive oil or rapeseed oil [43][44][45][46]. The disagreement between the present results and those above-mentioned is well explainable by different vitamin E concentrations of the diets.…”
Section: Effect Of Different Fats On the Susceptibility Of Ldl To Lipmentioning
confidence: 76%
“…In contrast to erythrocytes, the fatty acid composition of LDL was neither influenced by the type of fat nor by the vitamin E supply. The fatty acid composition of LDL is of particular physiological significance because it influences the susceptibility of LDL to lipid peroxidation [e. g. [16][17][18] [12,13]. * mg α-tocopherol equivalents per kg; a, b, c -significantly different by Fisher's multiple range test (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The last parameter is of particular physiological significance because it has been demonstrated that oxidatively modified LDL plays an important role in the pathogenesis of atherosclerosis [14,15]. It is known that the susceptibility of LDL to lipid peroxidation is influenced by several nutritional factors, particularly by dietary fats and antioxidants [16][17][18][19]. Fats with high levels of polyunsaturated fatty acids have been shown to increase the susceptibility of LDL to lipid peroxidation in various species whereas fats with high levels of saturated or monounsaturated fatty acids reduce it [16,17,20,21].…”
mentioning
confidence: 99%
“…Increased concentrations of α-tocopherol in plasma and LDL of rats fed the coconut oil diets supplemented with pure or oxidized cholesterol in Experiment 2 relative to rats fed the coconut oil diets without cholesterol in Experiment 1 may be due to their higher lipid concentrations in plasma and LDL. A strong relationship exists between the concentration of tocopherols and the concentration of total lipids in plasma [34]. The finding that an increase of the dietary vitamin E concentration from 40 to 240 mg/kg failed to reduce the concentrations of 7β-OH-Chol in liver, LDL and erythrocytes suggests that a dietary vitamin E concentration of 40 mg/kg provided maximum protection of cholesterol in these samples against oxidation even in the case of fish oil as dietary fat.…”
Section: Discussionmentioning
confidence: 97%